A conditional two‐hybrid (C2H) system for the detection of protein–protein interactions that are mediated by post‐translational modification. Issue 7 (25th February 2013) - Erce, Melissa A.; Low, Jason K. K.; Hart‐Smith, Gene; Wilkins, Marc R.
<x xml:space="preserve">Abstract</x> The original bacterial two‐hybrid system is widely used but does not permit the study of interactions regulated by PTMs. Here, we have built a conditional two‐hybrid (C2H) system, in which bait and prey proteins can be co‐expressed in the presence of a modifying enzyme such as a methyltransferase, acetyltransferase, or kinase. Any increase or decrease in interaction due to the modification of the proteins can be measured by an increased or decreased level of reporter gene expression. The C2H system is comprised of eight new vectors based on the Novagen Duet co‐expression plasmids. These vectors include two multiple cloning sites per vector as well as a hexahistidine tag or S‐tag to aid in purification, if desired. We demonstrate the use of the C2H system to study the dimerization of the yeast protein Npl3, which is increased when methylated by the methyltransferase Hmt1.